2012
DOI: 10.1177/1403494812449925
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences with metaphors in a solution-focused approach to improve self-management skills: A qualitative study

Abstract: The metaphor "Captain of the ship" was experienced as strengthening the messages from the solution-focused approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Consistent with our findings, other studies have demonstrated that the use of pictures and game elements in patient education is a promising method to support educators in facilitating person-centredness and active involvement. 17,[24][25][26] Examples include the DESMOND program, the EMMA program and the Conversation Map tool. [25][26][27] In addition, a feasibility study of the dialogue tools assessed here demonstrated that educators considered them helpful in creating participation and dialogue in patient education that focused on the daily lives of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, other studies have demonstrated that the use of pictures and game elements in patient education is a promising method to support educators in facilitating person-centredness and active involvement. 17,[24][25][26] Examples include the DESMOND program, the EMMA program and the Conversation Map tool. [25][26][27] In addition, a feasibility study of the dialogue tools assessed here demonstrated that educators considered them helpful in creating participation and dialogue in patient education that focused on the daily lives of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Tal pode ser efetuado incentivando o paciente a transmitir a sua informação sobre a doença, dúvidas e sentimentos, sem medo de ser julgado ou criticado. A literatura sugere que focar as metáforas durante a intervenção acarreta benefícios a longo prazo na autogestão (Grillo et al, 2016;Hinder & Greenhalgh, 2012;Solberg et al, 2014). Além disso, os profissionais de saúde deverão estar atentos às suas metáforas, que transmitem durante as consultas, pois poderão estar a influenciar a autogestão dos pacientes.…”
Section: Discussionunclassified
“…Metaphors are defined as perception and experience in the form of other words through objective visualization (24), and they subtly teach readers that everything requires a structure and that change is always possible inside any structure (25). According to prior studies, metaphors may be effective in the diagnosis of both severe and stable mental diseases such as schizophrenia, bipolar disorder, major depression, dysthymia (26), personal development, selfacceptance, sense of appreciating life, reduction of anxiety (27), cognitive development (28), self-concept development (29), and sense of responsibility (30).…”
Section: Introductionmentioning
confidence: 99%
“…Immediately they face even the most trivial obstacle, they feel serious distress. Under these conditions, IMT can help due to the promotion of a sense of responsibility in the field of health management (30). Moreover, it was also found that IMT can significantly affect the reduction of anxious over concern among drug addicts.…”
mentioning
confidence: 98%